The Influence of Aluminium Nanopowder Density on the Structure and Properties of its Combustion Products in Air; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Ilyin A. P. Aleksandr Petrovich (Advanced Materials and Alloys, Nanomaterials and Nanotechnology, 2016)
Title screen